Apospory and Diplospory in Diploid Boechera (Brassicaceae) May Facilitate Speciation by Recombination-Driven Apomixis-to-Sex Reversals - Carman, John G.; Mateo de Arias, Mayelyn; Gao, Lei; Zhao, Xinghua; Kowallis, Becky M.; Sherwood, David A.; Srivastava, Manoj K.; Dwivedi, Krishna K.; Price, Bo J.; Watts, Landon; Windham, Michael D. (Frontiers in Plant Science, 2019)
Multiple types of gametophytic apomixis (asexual seed formation) occur in angiosperms. These are differentiated by where and how the unreduced gametophyte (embryo sac) forms, a process referred to as apomeiosis. Unreduced gametophytes form directly from ameiotic megasporocytes (Antennaria-type diplospory), unreduced spores derived from 1st division meiotic restitutions (Taraxacum-type diplospory), or from cells of the ovule wall (apospory). Multiple types of apomixis occasionally occur in the same plant, which suggests that apomixis types might represent temporal or spatial shifts in the termination of sexual processes and the onset of apomixis processes. To better understand the origins and evolutionary implications of apomixis in Boechera (Brassicaceae), we determined apomeiosis types for 64 accessions representing 44 taxonomic units. Apospory and diplospory were equally common and generally produced reduced and unreduced pollen, respectively. Readily detectable levels of apospory and diplospory occurred simultaneously in individual plants of seven taxa. Apomixis in Boechera perpetuates otherwise sterile or semisterile interspecific hybrids (allodiploids) through multiple generations. Accordingly, ample time is available in these multigenerational clones for rare meioses to occur with haploid, intergenomically-recombined male and female gametes occasionally forming. Fusion of such gametes would produce recombined segmentally-autoploidized progeny. New genomically unique sexual species could then evolve if sex re-emerges among such progeny. We present evidence herein that such apomixis-facilitated speciation may be occurring in Boechera, and it might also be occurring in facultatively apomictic allodiploids of other angiospermous taxa.